Effect of Emotional Intelligence on Work Performance: A Comprehensive Analysis - Koutsioumpa, Eftichia (Technium Business and Management, 2023)
The present research thoroughly examines the impact of emotional intelligence on job performance. The significance of emotional intelligence concerning job satisfaction and its substantial influence on the performance of auditors has been well-documented. Moreover, a correlation exists between team emotional intelligence, team performance, and knowledge-sharing behavior. This study examines the correlation between team culture, knowledge sharing, emotional intelligence, and performance. Additionally, it underscores the significance of emotional and spiritual intelligence in augmenting work enthusiasm and auditor performance. Moreover, the analysis places significant emphasis on the impact of emotional intelligence, self-confidence, and leadership styles on the job performance of psychologists. Additionally, the investigation examines the influence of emotional intelligence on individual performance and the equilibrium between work and personal life. In general, the results emphasize the importance of emotional intelligence in enhancing job performance and the necessity for organizations to encourage the cultivation of emotional intelligence among their workforces.